Pengaruh Model Pembelajaran Project Based Learning bermuatan Cerita Rakyat Sasak terhadap Keterampilan Berbicara Siswa Kelas V SDN 15 Cakranegara - Ririn Tria Amanda; Moh. Irawan Zain; Muhammad Sobri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Speaking skills are one of the essential competencies that need to be developed among elementary school students. However, the speaking skills of fifth-grade students at SDN 15 Cakranegara still need improvement, as many students are not yet able to retell stories coherently, use appropriate intonation and expression, and speak confidently in front of the class. This study aimed to determine the effect of the Project Based Learning (PjBL) model integrated with Sasak folktales on the speaking skills of fifth-grade students at SDN 15 Cakranegara. This study employed a quantitative approach using a pre-experimental research design with a one-group pretest–posttest design. The sample consisted of 35 students selected through the saturated sampling technique. Data were collected through observations, interviews, and a speaking performance test and were analyzed using the N-Gain test. The learning activities involved the preparation of a story map based on the Sasak folktale Putri Mandalika, which served as a guide for students in retelling the story orally. The results showed that the mean pretest score increased from 67.29 to 81.14 in the posttest. The average N-Gain score was 0.43, which was categorized as medium. The improvement was reflected in the students’ ability to retell stories coherently, use clear language, demonstrate appropriate intonation and expression, understand the story content, and speak confidently in front of the class. Therefore, the Project Based Learning (PjBL) model integrated with Sasak folktales had a positive effect on the speaking skills of fifth-grade students at SDN 15 Cakranegara.